What drives waste sorting? A capability, opportunity, motivation, and behavior model analysis with hybrid modeling - Zhang, Beijia (Frontiers in Psychology, 2025)
To motivate urban residents to actively participate in waste sorting, this study aims to clarify the behavioral mechanisms driving residents' waste sorting behavior. Based on the Capability-Opportunity-Motivation-Behavior (COM-B) model, a comprehensive approach combining Structural Equation Modeling (SEM) and System Dynamics (SD) was employed to analyze the sample of Shanghai residents, examining the static and dynamic relationships between various factors and waste sorting behaviors. Results show that capability (knowledge), opportunity (infrastructure, subjective norms), and motivation (habit and intention) are positively correlated with sorting behavior, with the opportunity also has significant indirect effects on behavior via motivation. Notably, opportunity factors demonstrated stronger effect than capability and motivation. And when levels of capability, opportunity, and motivation increase over time, waste sorting behavior exhibits a nonlinear growth trend, accelerating from slow to fast. Therefore, in the cycle management of waste sorting, emphasis should be placed on later-stage efforts, prioritizing interventions that enhance opportunity factors to promote sustainable sorting behaviors. These findings offer theoretical and practical guidance for urban waste sorting management efforts.